Secondary Metabolite Profiles and Antibacterial Activity of Mitragyna speciosa Leaf Extracts According to Vein Color Variation - Febrina, Lizma; Hikmawan, Baso Didik; Adyma, M. Diva (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
Empirically, the three distinct color variants of M. speciosa leaves (red, white, and green) vein are widely utilized and reported to possess varying therapeutic properties. This difference in efficacy is hypothesized to be a direct consequence of variances in their respective secondary metabolite profiles. Given the limited research comprehensively characterizing these metabolites and assessing the comparative antibacterial activity of the three variants, this study aimed to identify the secondary metabolite groups present in the red, white, and green vein leaves and determine their antibacterial activity against Salmonella typhi and Staphylococcus aureus. The methodology involved maceration extraction using 96% ethanol, followed by phytochemical screening and antibacterial testing via the agar well diffusion method across concentrations of 5%, 10%, 20%, and 40%. The negative control (96% ethanol) and positive control (chloramphenicol) were simultaneously utilized. The results confirmed that all three vein samples contained major secondary metabolite groups, including alkaloids, flavonoids, phenolics, saponins, and tannins. Differential antibacterial activity was noted: the red vein extract showed the highest efficacy against S. typhi, achieving an inhibition zone of 4.68mm at 10%, while the green vein extract was most effective against S. aureus, with an inhibition zone of 5.00 mm at 10%. These findings definitively demonstrate a difference in antibacterial potency across the M. speciosa vein variants, collectively affirming their significant potential for development as antibacterial active agents.